Velocity characterization of solids in binary fluidized beds. (31st December 2021) - Roy, Sangram; Pant, Harish Jagat; Roy, Shantanu
Highlights: Measurement of velocity distributions through RPT showed hitherto unknown flow hydrodynamics in a binary fluidized bed. Effect of bed composition and particle size on the solids distribution and velocity ascertained. Solids flow pattern, mean and RMS velocity field and solids diffusivity presented. Significant database for model development for binary gas-solids flow. Abstract: Owing to challenges in velocimetry techniques, flow hydrodynamics of binary fluidized beds have remained largely unexplored. Thus, the present study seeks to address unraveling the velocity distributions in the binary fluidized bed of glass beads (0.5 and 2 mm) in fluidized with 10, 30, and 40% of coarser fractions. In order to decipher the velocity distributions, RPT was implemented, which yielded velocity distributions of both the 0.5 and 2 mm fractions. Distinct features of solids flow were observed with varying bed compositions. The mean velocity of finer flotsam (0.5 mm particles) fractions were found to diminish upon increasing the jetsam fraction (2 mm) due to variation in bed voidage. On the contrary, an enhanced coarser fraction of 2 mm particles in the bed diminished solids' fluctuation, which led to a corresponding reduction in the RMS velocities. Similar trends were also noted when solids' diffusivity was estimated for various bed compositions. Finally, the efficacy of this technique was independently verified qualitatively through mixing patterns obtained from 'bed freezing'.